2018
DOI: 10.1111/cei.13205
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of immune cell subsets in peripheral blood from patients with periodontal disease and healthy controls

Abstract: Periodontitis is a chronic inflammatory disease caused by the colonization of teeth by the bacterial plaque biofilm and the resultant host immune responses in adjacent periodontal tissues. Disease severity can vary dramatically between patients with periodontitis, with some subjects displaying inflammation without bony destruction (gingivitis), while others experience chronic progressive or rapidly aggressive gingival connective tissue damage and bone loss. To determine whether peripheral immune dysregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
1
18
1
Order By: Relevance
“…IFN-γ + cells were significantly lower at baseline, and 3-and 6-months post-treatment compared to health which is contrary to several studies in peripheral blood that reported higher CD4 + IFN-γ + cells in periodontitis compared to health (Chen et al, 2016;Schmidt et al, 2014) or reported no significant differences (Cheng et al, 2018;Lima et al, 2011;Okada et al, 2017). Fewer IFN-γ + expressing cells at baseline were mirrored by lower IFN-γ production upon stimulation with P. gingivalis.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…IFN-γ + cells were significantly lower at baseline, and 3-and 6-months post-treatment compared to health which is contrary to several studies in peripheral blood that reported higher CD4 + IFN-γ + cells in periodontitis compared to health (Chen et al, 2016;Schmidt et al, 2014) or reported no significant differences (Cheng et al, 2018;Lima et al, 2011;Okada et al, 2017). Fewer IFN-γ + expressing cells at baseline were mirrored by lower IFN-γ production upon stimulation with P. gingivalis.…”
Section: Discussioncontrasting
confidence: 90%
“…Thus, the healthy control group in this study includes health and localized gingivitis cases and the results should be interpreted in light of this (Cheng et al, 2018).…”
Section: Periodontitismentioning
confidence: 99%
See 1 more Smart Citation
“…Memory T‐cell profiles in peripheral blood in response to therapy are not well established in periodontitis. Previously, CD4 + CD45RA + naïve (Afar et al, 1992) and CD4 + CD45RO + antigen‐experienced memory cells (Afar et al, 1992; Aoyagi et al, 1995) were reported to be higher in periodontitis, whereas others reported that neither CD4 + CD45RA + naïve (Seymour et al, 1997) nor CD4 + CD45RO + memory cells (Cheng et al, 2018) were significantly different in chronic or aggressive periodontitis compared to health. Longitudinal studies have reported significantly increased CD4 + CD45RA + naïve cells post‐treatment (Kimura et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…IFN levels are increased in the gingival crevicular fluid 10,11 and saliva 12 from periodontitis patients. 13 IFN activation of stem cells from periodontal ligament, umbilical cord, and adipose tissue showed an immunosuppressive response by inhibiting proliferation of peripheral blood mononuclear cells (PBMCs). 14 Interestingly, the response of these cells appeared to depend on the presence of members of toll-like receptors (TLRs).…”
Section: Introductionmentioning
confidence: 99%